Metabolic effects of prazosin on skeletal muscle insulin resistance in glucocorticoid-treated male rats - Dunford, Emily C. (Am J Physiol Regul Integr Comp Physiol, 2017)
High-dose glucocorticoids (GC) induce skeletal muscle atrophy, insulin resistance, and reduced muscle capillarization. Identification of treatments to prevent or reverse capillary rarefaction and metabolic deterioration caused by prolonged elevations in GCs would be therapeutically beneficial. Chronic administration of prazosin, an α(1)-adrenergic antagonist, increases skeletal muscle capillarization in healthy rodents and, recently, in a rodent model of elevated GCs and hyperglycemia. The purpose of this study was to determine whether prazosin administration would improve glucose tolerance and insulin sensitivity, through prazosin-mediated sparing of capillary rarefaction, in this rodent model of increased GC exposure. Prazosin was provided in drinking water (50 mg/l) to GC-treated or control rats (400 mg implants of either corticosterone or a wax pellet) for 7 or 14 days (n = 5–14/group). Whole body measures of glucose metabolism were correlated with skeletal muscle capillarization (C:F) at 7 and 14 days in the four groups of rats. Individual C:F was found to be predictive of insulin sensitivity (r(2) = 0.4781), but not of glucose tolerance (r(2) = 0.1601) and compared with water only, prazosin treatment decreased insulin values during oral glucose challenge by approximately one-third in corticosterone (Cort)-treated animals. Cort treatment, regardless of duration, induced significant glycolytic skeletal muscle atrophy (P < 0.05), decreased IRS-1 protein content (P < 0.05), and caused elevations in FOXO1 protein expression (P < 0.05), which were unaffected with prazosin administration. In summary, it appears that α(1)-adrenergic antagonism improves Cort-induced skeletal muscle vascular impairments and reduces insulin secretion during an oral glucose tolerance test, but is unable to improve the negative alterations directly affecting the myocyte, including muscle size and muscle signaling protein expression.